IMPLEMENTATION AND EVALUATION OF BREAST CARE TO THE CHILDBED MOTHER IN COMBINED WARD OF PUSKESMAS TEGALREJO YOGYAKARTA, INDONESIA - Rosmawati Rosmawati; Fitri H. Susanto; Retno Purwanti (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Breast care is an act carried out at the time pregnant and nursing mothers. It aimed to improve blood circulation and to prevent problems that often arise at the time of breastfeeding includingthe frequent occurrence of mastitis (inflammation of the breast) in postpartum mothers. Breast care is often overlooked by mothers who are breastfeeding because after giving birth they have no knowledge to breast care. Aims: This study aims to investigate the implementation of the breast treatment by health workers and to examine the implementation by the breast care postpartum mothers at health centers Tegalrejo. Methods: This research is a descriptive nonexperimental with cross sectional. Out of 104 puerperal women in health centers Tegalrejo, a total of 20 puerperal women who gave birth in June 2016 was selected followed 10-15 % of total population by Arikunto’s formula. There were 15 health providers also involved in the study. Analysis of the data in this study used a computerized system with Excel program, after the data was collected in the tabulation, then both of the officer and postpartum mother sought to see the picture at the health center Evaluation of Breast Care Tegalrejo using frequency distribution. Results: The results of this study showed that through the implementation of Breast Care, implemented by health personnel at health centers Tegalrejo, of 15 health providers obtained good results, and of 20 respondents obtained medium result. Conclusion: The conclusion that the breast care Implementation according to the perception of puerperal women and health workers, the fact that there is in the assessment indicate the category of no good, only seven people puerperal women (35%) who received breast care.